IMPLEMENTATION OF LITERACY CULTURE IN VOCATIONAL SCHOOLS TO INCREASE STUDENTS' LEARNING MOTIVATION - Sumarni, Ai (Universitas Pendidikan Indonesia, 2024)
This research aims to describe how literacy culture is implemented in vocational schools to increase student learning motivation. The research method uses participatory observation, where researchers directly observe daily activities in vocational schools related to the implementation of literacy culture. Respondents consisted of three teachers and 90 students from Computer Network and Telecommunications Engineering (TJKT) at SMKN 1 Gunungguruh Sukabumi. The research results show that by using a classical and independent approach, the school creates a learning environment that supports the development of students' literacy skills. The classical approach involves teachers in direct teaching and intensive guidance on reading, writing and text analysis techniques, while the independent approach provides opportunities for students for independent exploration in reading and writing. This combination not only improves students' literacy skills but also stimulates their creativity and increases motivation towards the learning process.